Globalization Past, Present, Future - Steger, Manfred B.; Benedikter, Roland; Pechlaner, Harald; Kofler, Ingrid (University of California Press, 2023)
Since the end of the Cold War, globalization-the process and the idea-has been reshaping the world. Global studies scholarship has emerged to make sense of the transnational manifestations of globalization: economic, social, cultural, ideological, technological, environmental, and postcolonial. But a series of crises in the first two decades of the twenty-first century has put the neoliberal globalization system of the 1990s under severe strain. Are we witnessing a turn toward "deglobalization," intensified by the COVID-19 pandemic and the war in Ukraine or a moment of "reglobalization," spearheaded by digital technology? The contributors to this book employ transdisciplinary research to assess past developments, the current state, and future trajectories of globalization in light of today's dynamics of insecurity, volatility, and geopolitical tensions. "Globalization offers a long overdue framework for understanding the continuities and discontinuities of global dynamics, with scholarship from every corner of the globe. For the first time, we have a volume that brings the local into conversation with the global across domains of economics, politics, culture, and technology, while attending to the through lines from past to present. A must-read for scholars and students of globalization." - SARA R. CURRAN, Associate Vice Provost for Research at the University of Washington and section editor of Global Perspectives